Single-cell RNA-sequencing identifies various proportions of excitatory and inhibitory neurons in cultured human fetal brain cortical tissues - Rong Liu; Wei Dong; Dan Xiong; Lanqi Hu; Haoran Zhang; Xiaoping Yuan; Zhonghui Tang; Fang Fu; Xin Yang; Xia Wu (Frontiers in Neuroscience, 2023)
IntroductionCortical neural progenitor cells possess the capacity to differentiate into both excitatory and inhibitory neurons. However, the precise proportions in which these progenitor cells differentiate remain unclear.MethodsHuman fetal prefrontal cortical tissues were collected at various fetal stages and cultured in vitro. Bulk and single-cell RNA sequencing techniques were employed to analyze the resulting neuronal cell types, cell proportions, and the expression levels of cell-type marker genes.ResultsThe culture of fetal prefrontal cortex tissues obtained at gestation weeks 11 and 20 predominantly consisted of excitatory and inhibitory neurons, respectively. This abrupt transition in cell proportions was primarily driven by the differential lineage specificity of neural progenitors in the fetal cortical tissues at distinct stages of fetal brain development. Additionally, it was observed that the transcriptional profiles of cultured fetal cortical tissues were strongly influenced by the presence of FGF2.DiscussionThis study presents a novel strategy to obtain excitatory and inhibitory neuronal cells from the culture of fetal cortical tissues. The findings shed light on the mechanisms underlying neurogenesis and provide an approach that might contribute to future research investigating the pathophysiology of various neural disorders.